Bridging in vitro Electrophysiology and in vivo Behavior in Zebrafish Models of Autism Spectrum Disorder (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition characterized by challenges in social interaction, communication, and the presence of restricted and repetitive behaviors. While the neurobiological underpinnings of ASD remain elusive, understanding the function of individual neurons and their integration into circuits is critical. The zebrafish (Danio rerio) offers a powerful model system for dissecting neural circuit function due to its genetic tractability, external development, larval transparency, and conserved neuroanatomy. This presentation highlights the utility of the zebrafish model for investigating ASD-relevant neural circuitry through a combined in vitro and in vivo approach. We focus on isolating specific neuronal populations from zebrafish models of ASD to perform in vitro electrophysiological recordings, characterizing their intrinsic electrical properties and synaptic signaling deficits at the single-cell level. These in vitro findings regarding altered neuronal excitability and connectivity are then validated in vivo by assessing corresponding behavioral phenotypes in intact zebrafish larvae using established paradigms for social interaction, locomotion, and sensory processing. By correlating cellular-level electrical dysfunction observed in vitro with circuit-level activity and complex behaviors in vivo, we aim to bridge the gap between molecular/cellular deficits and the emergent behavioral characteristics of ASD. This integrated approach using the zebrafish model provides a valuable platform for identifying specific neuronal contributions to ASD pathophysiology and offers potential avenues for high-throughput screening of therapeutic interventions targeting neuronal function. The insights gained from these studies contribute to a more comprehensive understanding of ASD neurobiology and facilitate the translation of findings towards clinical applications.
Keywords: Autism Spectrum Disorder; zebrafish model; electrophysiology; neuronal excitability